Ответ:
Объяснение:
sina+sinb=2sin((a+b)/2)cos((a-b)/2)
cosa-cosb=-2sin((a+b)/2)sin((a-b)/2)
sina+sinb-sin(a+b)=2sin((a+b)/2)cos((a-b)/2)-2sin((a+b)/2)cos((a+b)/2)=
=2sin((a+b)/2)(cos((a-b)/2)-cos((a+b)/2)=
=2sin((a+b)/2)*2sina/2sinb/2=4sin(a/2)sin(b/2)sin((a+b)/2)
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
Объяснение:
sina+sinb=2sin((a+b)/2)cos((a-b)/2)
cosa-cosb=-2sin((a+b)/2)sin((a-b)/2)
sina+sinb-sin(a+b)=2sin((a+b)/2)cos((a-b)/2)-2sin((a+b)/2)cos((a+b)/2)=
=2sin((a+b)/2)(cos((a-b)/2)-cos((a+b)/2)=
=2sin((a+b)/2)*2sina/2sinb/2=4sin(a/2)sin(b/2)sin((a+b)/2)